KLASIFIKASI KONTEN POST PADA MEDIA SOSIAL INSTAGRAM PERGURUAN TINGGI XYZ MENGGUNAKAN ALGORITMA NAIVE BAYES - Nova Agustina; Andrian Cahyanto; Joko Herwanto; Ratih Ratnasari; Sintia Dewi (Jurnal Ilmiah Teknologi Infomasi Terapan, 2019)
Social media has an important role as a communication tool to share information and connect with each other. social media is used as a space to interact with people from various walks of life. One of the most widely used social media in the world, including in Indonesia is Instagram. This study aims to find out what post content is most optimal in Online Engagement. This study uses post data uploaded by XYZ Higher Education Instagram accounts from September 22 2015 to June 4, 2019. Post analyzed in this study amounted to 426 post content. A comparative test was conducted to see the difference between online engagement between post content. The results of this study indicate that post type and post time (month and day) have a significant effect on online engagement (likes and comments). While the months that have the most significant influence on likes and comments are March, June and July. Thursday, Friday and Saturday are days that have a significant influence on likes and comments.